Mobile Application with AR as a Strategy to Improve the Marketing Process in a Dental Center - Beltozar-Clemente, Saul (2023)
The post-pandemic period brought with it new challenges for both businesses and private health centers, many of which were affected by the loss of customers. In the case of dental centers, many were affected by the distrust of customers, since activities performed in the oral cavity exposed them to the contagion of Covid-19. This research work proposes the implementation of a mobile application with Augmented Reality (AR) as a strategy for digital marketing immersion, with the aim of achieving a dynamic approach to the services provided in the dental center to customers, this is through the use of this technology in conjunction with social networks, contributing to the improvement of the business and building trust with customers. The application was developed under the Mobile-D methodology with a layered system development architecture, having as indicators the time of elaboration of the advertisement, the cost of information material, the time to inform the services, and the level of customer satisfaction. Finally, the results revealed that the time of elaboration of the advertisement decreased from 25 hours to 14 hours, the cost of informative material was considered “low“ since the implementation of the application turns out to be economic, and the time to inform the services in its marketing process went from 30 min to 19 min with the use of the application, finally, the customer satisfaction increased being considered in 87% between “Good“ and “Excellent“.